A Security Enhanced Password Authentication and Update Scheme Based on Elliptic Curve Cryptography - Hang Tu (Indonesian Journal of Electrical Engineering and Computer Science, 2014)
As two fundamental requirements to ensure secure communications over an insecure public network channel, password authentication and update of password have received considerable attention. To satisfy the above two requirements, Islam et al. proposed a password authentication and update scheme based on elliptic curve cryptography. They claimed that their scheme could withstand various attacks. Unfortunately, He et al. found Islam et al.’s scheme is still vulnerable to off-line password guessing attack and stolen-verifier attack. In this paper, a security enhanced scheme is developed to eliminate the identified weaknesses. The analysis shows that our scheme can not only overcome the security vulnerability in Islam et al.’s scheme, but also has better performance than their scheme. Then our scheme is more suitable for practical applications.